ALTERNATIVE TYPES OF EMPLOYMENT IN THE CONTEXT OF HUMAN POSSIBILITIES EXTENSION IN THE DIGITAL ECONOMY (CASE OF UKRAINE) - Brintseva, O.; Glybovets, V. (Scientific Journal of Pedagogy and Economics, 2020)
As a result of the Fourth Industrial Revolution, the global spread of digital technologies and automation processes have led to a steady decline in staffing needs. Thus, in the near future only the most competitive part of the working population will have the opportunity for productive, well-paid, and stable employment. The problem of ensuring social wellbeing by providing livelihoods to the general public, expanding opportunities for self-realization, and the most productive use of labor potential can be partially solved by the implementation of unconditional basic income. However, for many countries around the world, as proven by experiments, this decision could be quite expensive and controversial. In this context, the main positive and negative socio-economic, demographic, and political aspects of the implementation of unconditional basic income in Ukraine were identified. A research has been made on alternative types of employment (freelance, gig employment, crowd employment), as well as on the opportunities for self-realization and implementation of activities useful to society in the digital economy (implementation of social projects; volunteering, participation in social projects; lifelong learning; raising children and care for the elderly, etc.) as promising areas of human potential use in society.